The future of elder care in Italy in COVID-19 pandemic times: Socio-economic considerations - Chiara Bugariand Giovanni Lamura (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Target: Following the Covid-19 pandemic, the category of elderly people, in particular those who are not self-sufficient, is among those most affected in Italy. It is therefore urgent to identify innovative methods of support, in order to ensure a better quality of life in such a complex period from an epidemiological but also a socio-economic point of view. At the center of these reflections is home care for the non self-sufficient elderly, analyzed through the role played by crucial actors such as private paid assistants and family caregivers, in order to understand how to best guarantee it in delicate circumstances.  Methods: Bibliographic research on the home situation of the elderly non self-sufficient population, through the comment of secondary statistical data updated on 1 July 2020.  Results: From the limited data found, major problems are related first and foremost to the fear of and economic problems due to job losses of family members, who often contribute and support the assistance of the elderly from an economic point of view, with consequent difficulties in supporting dependent older relatives. The pandemic has accentuated and highlighted pre-existing socio-economic problems, but also made critical situations that were previously not too worrying.  Conclusion: The fear of social isolation due first to the pandemic and then to economic problems denotes an urgent need for public support, underlining at the same time the extreme importance of private home assistance. It is therefore necessary to invest in this sector, given the vastness of the elderly population in Italy, also through the preliminary collection of more targeted and updated data on the condition of frail older people and their families, in order to bring concrete and innovative solutions in the field elder care.